2003
DOI: 10.1128/jcm.41.10.4594-4599.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genome Type Analysis of Adenovirus Types 3 and 7 Isolated during Successive Outbreaks of Lower Respiratory Tract Infections in Children

Abstract: Adenovirus is an important cause of respiratory infections in infants and children. Fifty-one serotypes have been identified, and adenovirus type 3 (Ad3) and Ad7 have often been associated with outbreaks of severe respiratory tract infections. Each serotype can be further divided into genome types based on the patterns of digestion of their DNAs with restriction enzymes. DNA restriction analysis was performed with 56 strains of Ad3 and 98 strains of Ad7 by using 12 restriction enzymes recognizing 6 bp (BamHI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
114
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 36 publications
(50 reference statements)
6
114
1
Order By: Relevance
“…This represented the highest significant difference with other age groups (X 2 =10.436, P<0.01). Again results of our study showed that most patients with HAdV infection were younger than 5 years (85.5%), which is a similar value were obtained in previous studies [32][33][34]. The result of the present study indicates that HAdVs infections acquisition are significantly depended on children age, while 36% were found in children aged ≤ 6 years.…”
Section: Molecular Diagnosis Of Human Adenovirus In Children With Uppsupporting
confidence: 80%
“…This represented the highest significant difference with other age groups (X 2 =10.436, P<0.01). Again results of our study showed that most patients with HAdV infection were younger than 5 years (85.5%), which is a similar value were obtained in previous studies [32][33][34]. The result of the present study indicates that HAdVs infections acquisition are significantly depended on children age, while 36% were found in children aged ≤ 6 years.…”
Section: Molecular Diagnosis Of Human Adenovirus In Children With Uppsupporting
confidence: 80%
“…These distinctions correlate strongly with antigenicity, clinical presentation, and epidemiological character (30), and the same groups are similarly clustered on the basis of genetic homology (11). Under most circumstances, the clinically important Ad species are those associated with febrile respiratory disease (AdB1, AdC, and AdE) since these can cause widespread outbreaks with severe clinical presentations, including viral pneumonia and death (17,20,25,29).…”
mentioning
confidence: 99%
“…These two serotypes are often responsible for the most severe respiratory symptomologies associated with adenoviral infection (12,16). Outbreaks of Ad3 and Ad7 occur worldwide and have been documented in Japan (20), Korea (13), the United Kingdom (7), the United States (4, 9), South America (17), China (21), and elsewhere. AdB also includes the less common serotypes 11,14,16,21,34, and 35, all of which have been, at least occasionally, associated with respiratory disease (4,9,28).…”
mentioning
confidence: 99%
“…For example, after cough and shortness of breath, the main symptoms associated with HAdV-B14p1 infection in a recent community outbreak in Oregon were vomiting and diarrhea (44). There are several reports from different Asian countries that HAdV-B3 infection in children is associated with acute gastroenteritis (10,33,37,45,46).…”
mentioning
confidence: 99%